Velar and Uvular Stop Production in Qur’anic Recitation: A Phonetic Study Across Three Speaker Groups - Fatimah Azzahra; Syihabuddin; Nalahuddin Saleh (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study examines the acoustic realization of the velar stop /k/ and the uvular stop /q/ in the recitation of Surah Al-‘Alaq, with particular attention to the role of articulatory training. Using acoustic analysis, the study investigates spectral and temporal parameters across readers with different levels of tahsin training, focusing on the second formant (F2) and segmental duration as correlates of place-of-articulation contrast. The results indicate that the distinction between /k/ and /q/ is most consistently reflected in spectral properties. The uvular stop /q/ shows systematically lower F2 values than /k/, reflecting posterior tongue dorsum retraction associated with uvular articulation, even within the highly regulated context of Qur’anic recitation. In contrast, segmental duration does not display a consistent distinction between the two consonants, suggesting that temporal cues are strongly influenced by suprasegmental constraints such as tempo regulation and rhythmic organization. Differences across participant groups further suggest that articulatory training contributes to greater stability in spectral realization. Readers with tahsin training demonstrate more consistent F2 patterns for /q/ than pre-tahsin learners, indicating improved control over articulatory gestures critical for posterior consonant production. Overall, the findings show that spectral cues provide a more reliable basis for distinguishing velar and uvular stops than temporal measures in recitational speech, with important implications for tahsin instruction.